2022
DOI: 10.3389/fimmu.2021.798207
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Functional Specific Antibodies, IgG-Secreting Plasmablasts and Memory B Cells Following BCG Vaccination

Abstract: Tuberculosis (TB) is a major global health problem and the only currently-licensed vaccine, BCG, is inadequate. Many TB vaccine candidates are designed to be given as a boost to BCG; an understanding of the BCG-induced immune response is therefore critical, and the opportunity to relate this to circumstances where BCG does confer protection may direct the design of more efficacious vaccines. While the T cell response to BCG vaccination has been well-characterized, there is a paucity of literature on the humora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…The cellular immune response is critical in host resistance to M. tuberculosis . However, more and more evidence indicates that the humoral immune response also plays an essential role in killing M. tuberculosis ( Bitencourt et al., 2021 ; Gong et al., 2022 ; Nziza et al., 2022 ). This study explored the humoral immunity induced by the MP3RT vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular immune response is critical in host resistance to M. tuberculosis . However, more and more evidence indicates that the humoral immune response also plays an essential role in killing M. tuberculosis ( Bitencourt et al., 2021 ; Gong et al., 2022 ; Nziza et al., 2022 ). This study explored the humoral immunity induced by the MP3RT vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In another NHP study, intravenous BCG drove superior antibody responses in the plasma and lungs of rhesus macaques compared to the traditional intradermal route and the IgM titers negatively correlated with Mtb burden (58). In a combined human and NHP study, BCG-driven induction of specific antibodies was shown to be comparable across humans and macaques, both in magnitude and the range of mycobacterial fractions (59). The study also showed the rapid and transient induction of antibody-secreting plasmablasts following BCG vaccination and via the use of in vitro functional assays identified a potential FcgR-mediated contribution of antibodies to the control of mycobacterial growth.…”
Section: B Cells and Antibody Responses To Bcg Vaccinationmentioning
confidence: 97%
“…Moreover, antibodies are produced against a variety of M. tuberculosis antigens in human and animal models, and total and mycobacterial-specific antibody glycosylation patterns correlate with the effective control of M. tuberculosis infection and may distinguish patients with active TB disease from subjects with latent TB infection (LTBI) [ 11 , 17 ]. Finally, a recent study in rhesus macaques found that following intravenous BCG vaccination, IgM antibody levels in the plasma and bronchoalveolar lavage were the best indicators of protection against M. tuberculosis challenge [ 18 ].…”
Section: Introductionmentioning
confidence: 99%